Preparation and adsorption performance of cellulose nanofibrils/polyvinyl alcohol composite gel spheres with millimeter size. (1st February 2022) - Yi, Qing; Lu, Sheng; Fan, Yutong; Cheng, Dehua; Wang, Xumei; Cheng, Shaoling; Xie, Hongxiang
Abstract: Wastewater treatment is a huge problem facing human beings. The development of recyclable and efficient adsorption materials is of great benefit to solve the problem. Based on the biodegradable cellulose nanofibers (CNFs) derived from biomass resources, the large sized CNFs/PVA composite hydrogel spheres (CV-HSs, 1–3 mm) were successfully prepared by the inverse suspension pellet-forming technology using the polymers as raw materials, and another hydrophobic CNFs/PVA composite aerogel spheres (HCV-ASs) were also obtained by lyophilization and followed silylation of as-prepared CV-HSs. The CV-HSs showed excellent adsorption properties for simulated pollutants, including Cu 2+, phenol and aniline in water. The maximum absorption capacity of CV-HSs was 17.22 mmol/g for Cu 2+, 176.72 mg/g for phenol and 341.93 mg/g for aniline respectively. The HCV-ASs exhibited good absorption properties for weak polar organic solvents, such as petroleum ether, ethyl acetate and toluene. In summary, two kinds of large-sized CNFs/PVA composite gel spheres were successfully fabricated, and exhibited good adsorption properties for organic pollutants and heavy metal ions, indicating their potential for wastewater treatment. Graphical abstract: In this paper, hydrogel spheres and hydrophobic aerogel spheres via combining CNFs with PVA were successfully prepared, which showing excellent adsorption capacity for wastewater pollutants. Unlabelled Image Highlights: CNFs/PVA composite gel spheres with the diameter of 1–3 mm were successfully prepared. Silane modification can enhance the thermal stability of CNFs/PVA composite materials. CV-HSs have excellent adsorption properties for Cu 2+, phenol and aniline in water. HCV-ASs exhibit good absorption properties for weak polar organic solvents.